2022
DOI: 10.1039/d1cc05791j
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the role of zinc precursor during the synthesis of the core of III–V QDs

Abstract: Three roles of zinc precursor in the synthesis of III–V QDs: a reaction suppressant, a size regulator, and a dopant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…27−29 The localization of Zn 2+ either on the QD surface or in its volume depends on several parameters, such as the temperature, concentration, and ligation, governing the reactivity of the Zn precursor during the reaction. 29,30 Therefore, in some conditions, Zn 2+ can also act as a p-type dopant for InP QDs introducing shallow defects, which lead to spectral broadening. 31 Talapin and co-workers demonstrated that Zn-doping of InP QDs leads to lattice disorder generating localized hole states close to the valence band edge, which are responsible for the observed red-shifted emission and large Stokes shift as well as the anomalous broadening of the photoluminescence excitation (PLE) spectra.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…27−29 The localization of Zn 2+ either on the QD surface or in its volume depends on several parameters, such as the temperature, concentration, and ligation, governing the reactivity of the Zn precursor during the reaction. 29,30 Therefore, in some conditions, Zn 2+ can also act as a p-type dopant for InP QDs introducing shallow defects, which lead to spectral broadening. 31 Talapin and co-workers demonstrated that Zn-doping of InP QDs leads to lattice disorder generating localized hole states close to the valence band edge, which are responsible for the observed red-shifted emission and large Stokes shift as well as the anomalous broadening of the photoluminescence excitation (PLE) spectra.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Furthermore, zinc chloride is generally added in significant amounts (typically with a Zn/In ratio of around 5:1) to aminophosphine-based syntheses of InP QDs since it has been noted that its presence strongly reduces the size distribution and improves the PL properties . ZnCl 2 has been shown to influence the synthesis reaction kinetics, generally leading to smaller-sized InP QDs of lower-size dispersion. , It can also play the role of a Z-type (Lewis acid) ligand for the QD surface, improving its passivation. The localization of Zn 2+ either on the QD surface or in its volume depends on several parameters, such as the temperature, concentration, and ligation, governing the reactivity of the Zn precursor during the reaction. , Therefore, in some conditions, Zn 2+ can also act as a p-type dopant for InP QDs introducing shallow defects, which lead to spectral broadening . Talapin and co-workers demonstrated that Zn-doping of InP QDs leads to lattice disorder generating localized hole states close to the valence band edge, which are responsible for the observed red-shifted emission and large Stokes shift as well as the anomalous broadening of the photoluminescence excitation (PLE) spectra .…”
Section: Introductionmentioning
confidence: 99%
“…For the synthesis of InP cores, (TMS) 3 P was added into the mixture of indium acetate, zinc undecylenate, PA, and ODE at room temperature, and then the solution was heated up to 290 °C to form InP cores. Zinc carboxylates can reduce the reactivity of P precursors, which is necessary to obtain the small-sized and uniform green-emitting InP QDs. , It is worth noting that the insufficient Zn ions are mainly covered on the surfaces of InP cores and not incorporated into the lattices during the nucleation process, which has been reported in previous studies. , To explore the influence of both the external ions on the InP cores, the purified InP nuclei were mixed with Zn­(St) 2 (Zn–InP) and TOP-Se (Se–InP) at 290 °C, respectively. The synthesis details are shown in the Supporting Information.…”
Section: Resultsmentioning
confidence: 99%
“…15,16 It is worth noting that the insufficient Zn ions are mainly covered on the surfaces of InP cores and not incorporated into the lattices during the nucleation process, which has been reported in previous studies. 17,18 To explore the influence of both the external ions on the InP cores, the purified InP nuclei were mixed with Zn(St) 2 (Zn−InP) and TOP-Se (Se−InP) at 290 °C, respectively. The synthesis details are shown in the Supporting Information.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Previous studies indicate that Zn 2+ ions incorporate as substitutional dopants into the InP QDs crystal lattice, forming shorter Zn−P bonds compared to In−P bonds and simultaneously passivate surface defects and trap states 51,52 and Zn 2+ ions are more abundant on the surface of In(Zn)P QDs. 53 Subsequently, a thin Se-rich layer is incorporated into the In(Zn)P QDs by rapidly injecting a TOP-Se precursor, resulting in the formation of an alloyed In(Zn)PSe. To avoid the generation of separate ZnSe QDs and In(Zn)PSe@ZnSe core− shell structure, the reaction temperature was maintained below 180 °C after the TOP-Se precursor injection.…”
Section: Resultsmentioning
confidence: 99%